IMUNISASI: FAKTOR-FAKTOR ORANG TUA MENGAMBIL KEPUTUSAN PEMBERIAN IMUNISASI - Ayuni Nur Rachmah; Annisa Nurida; Uning Marlina (Universitas Muhammadiyah Surabaya, 2023)
Every year more than 1.4 million children worldwide die from diseases that can be prevented by immunization. An estimated 1.7 million deaths or 5% occur in children in Indonesia are due to PD3I. Immunization is the primary prevention against infectious diseases. The preparation of this literature review aims to determine what factors influence the decision of parents to immunize their children because in Indonesia itself there is still a low immunization coverage.Â Search and collection of literature studies using relevant keywords (